Help your communities grow! - Evellin, Benoît (Septentrio Conference Series, 2021)
We all have been newcomers one day, and gradually we managed to find our way to become experienced users. But how many promising newcomers have abandoned this same journey because they didn't understand our tools or our policies, or lacked human-to-human support? The Wikimedia Foundation Growth team is working on a set of tools that help communities to welcome newcomers and grow wikis in size and quality. These features have been shown to increase the activation, retention, and edit volume of newcomers. Newcomer homepage: a special page that hosts the "Newcomer tasks" and is a good place for a newcomer to get started. The homepage gives access to many resources, including a link to a volunteer mentor who would reply to their questions. Newcomer tasks: a feed of suggested edits that help newcomers learn how to make simple edits on their preferred subjects. Newcomers have been making productive edits through this feed! The feed is located on the homepage, as the starring feature. Help panel: a platform to provide resources to newcomers while they are editing. When newcomers work on "Newcomer tasks", the help panel guides them on what to do. All of these features are available right now, on both desktop and mobile: communities can request their deployment if they want to try them. This presentation will be about discovering the Growth tools, know their benefits, and see how to implement them in order to increase chances to grow your community in a qualitative way. We will also show the future of these features.